2001
DOI: 10.1002/ijpg.231
|View full text |Cite
|
Sign up to set email alerts
|

Leaving Home in Europe: The Experience of Cohorts Born Around 1960

Abstract: In the paper we analyse the leaving-home experience of men and women born around 1960 in 16 European countries. We use extensive empirical evidence from Fertility and Family Survey data, providing a largescale comparison. We focus on some key indicators of the process of leaving home: the timing, sequencing and synchronisation of leaving home with the end of education and the formation of a ®rst union. As far as these dimensions of leaving home are concerned, Europe appears to be extremely heterogeneous, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
168
0
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(184 citation statements)
references
References 22 publications
7
168
0
9
Order By: Relevance
“…In the UK young adults have tended to exhibit earlier home-leaving than many other European countries (Aassve et al 2002;Billari, Philipov, and Baizan 2001). However, this may be changing as a consequence of the extension of young adults' dependency, or 'semi-dependency', on their parents (Furlong and Cartmel 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the UK young adults have tended to exhibit earlier home-leaving than many other European countries (Aassve et al 2002;Billari, Philipov, and Baizan 2001). However, this may be changing as a consequence of the extension of young adults' dependency, or 'semi-dependency', on their parents (Furlong and Cartmel 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that across the countries considered in the present investigation there are very di erent cultural histories, labor market institutions and social characteristics. Such di erences may play a lasting role in explaining the substantial heterogeneity in the ages of children when they leave home across Europe (Aassve et al 2002;Billari et al 2001) and may not be entirely captured by including country xed e ects in the model estimated using the pooled sample from multiple countries. To mitigate this concern, I conduct the main analysis by European region.…”
Section: Retirement In Europe (Share) This European Dataset Has Thrementioning
confidence: 99%
“…During the 1980s the age of leaving the parental home was increasing in many developed countries after a period of decline (Billiari et al 2001;Molgat 2002;Young 1987;Corijin & Klijzing 2001). A recent Australian study has found that leaving home still occurs during early adulthood and has not experienced the delay felt in other demographic or lifecourse events.…”
Section: Age Left Parental Homementioning
confidence: 99%